The Right Of Hot Pursuit At Sea Between Legal Text And Practical Reality - أحمد , بسام; زوباري, هشام (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The right of hot pursuit at sea is one of the mechanisms that enable the coastal state to enforce its laws in the water areas that are subject to its sovereignty or jurisdiction in a manner that ensures the proper application of these laws by ships of other countries, but whoever has the right should not abuse it, the practice of hot pursuit is restricted by controls And conditions for the coastal state to observe out of respect for the international conventions that balance the right of the coastal state with the freedoms of other countries, but the practical reality raises many challenges facing the right of hot pursuit caused by the emerging international conditions and the growing human needs for more resources provided by the seas.